Psychometric properties of the EQ-5D-5L in diabetes mellitus patients in Spain - Amaia Bilbao-González; Marta González-Sáenz de Tejada; Montse Ferrer; Yolanda Ramallo-Fariña; Miguel Paja-Fano; Carlos García-Forero; Daniela Mestre; Iñigo Gorostiza-Hormaetxe (Journal of Patient-Reported Outcomes)
Abstract Background The EQ-5D-5L five-dimensional instrument, is one of the most widely used generic preference-based questionnaires to measure health-related quality of life and to estimate utility indices for use in economic evaluation. This study aimed to assess the psychometric properties of the Spanish EQ-5D-5L questionnaire in patients with Diabetes Mellitus (DM) assessing reliability, validity, and item-level properties such as item functioning. Methodology We included 133 patients with DM who completed the EQ-5D-5L, the Audit on Diabetes-Dependent Quality of Life (ADDQoL), the Hospital Anxiety and Depression Scale (HADS), one question about general health and sociodemographic, and clinical data. The reliability was assessed by Cronbach’s alpha, and the item functioning by the item response theory (IRT). Convergent validity was tested using the Spearman correlation coefficient between EQ-5D-5L, ADDQoL, HADS and the general health question. We examined known-groups validity by comparing the EQ-5D-5L scores between subgroups defined by age, gender, BMI, regular physical activity, disease duration, glycemic control by glycosylated blood hemoglobin (HbA1c) (%), type of DM, general health and anxiety and depression level using t-test, ANOVA, Wilcoxon or Kruskal-Wallis tests. Results The reliability was supported with a Cronbach’s alpha of 0.78. The IRT results supported the unidimensionality and showed adequate item functioning, except for the anxiety/depression dimension. The item with highest discriminatory power was usual activities dimension, followed by self-care and mobility dimensions. The EQ-5D-5L showed adequate convergent validity, with high correlation with the ADDQoL, HADS and general health. Older age, women, obese, no regular physical activity, ≥ 10 years of disease duration, poor glycemic control, poorer general health and higher anxiety and depression level linked with lower EQ-5D-5L scores. Conclusions These findings support the adequate psychometric properties of the EQ-5D-5L in patients with DM, supporting its use for clinicians and researchers as an outcome measure and for use in economic evaluation studies.